Male Female Voice Recognition As An Initial Design For Voice Authentication Alternatives - Setiawan, Hermawan; Tobing, Tio Hana Lolita Lumban; Marbun, Jonathan Sebastian; Manurung, Bahteramon Bintang Sanjaya; Putra, I Gede Maha; Dramaga, M. Rakhmat (International Conference on Sciences Development and Technology, 2022)
Artificial Intelligence (AI) technology has experienced a very rapid development, where AI has become a part of daily life. One of the applications of AI that has been widely implemented is the Voice Gender Recognition service. With the help of AI, it can be used to find out the gender of the voice sample uploaded to the application. Speech recognition is not something easy to do. Not a few did not manage to get the desired result.  This study is the first step that sound becomes a way of authenticating a person. Applications are built using the R language. CART models are used to make decision-making easier. A sample of 20 respondents was taken with various conditions when recorded. The final result of the application gets an accuracy percentage of 82%.Artificial Intelligence (AI) technology has experienced a very rapid development, where AI has become a part of daily life. One of the applications of AI that has been widely implemented is the Voice Gender Recognition service. With the help of AI, it can be used to find out the gender of the voice sample uploaded to the application. Speech recognition is not something easy to do. Not a few did not manage to get the desired result.  This study is the first step that sound becomes a way of authenticating a person. Applications are built using the R language. CART models are used to make decision-making easier. A sample of 20 respondents was taken with various conditions when recorded. The final result of the application gets an accuracy percentage of 82%.